Long-term effects of boxing and judo-choking techniques on brain function - Rodriguez, G.; Vitali, P.; Nobili, F.; Nobili, F. (The Italian Journal of Neurological Sciences, 1998)
Regional cerebral blood flow (rCBF) was measured by 133-xenon inhalation in 24 amateur and 20 professional boxers, and in 10 judoka. Results were compared with those from age- and sex-matched healthy controls. Eighteen boxers (9 amateurs and 9 professionals) and all judoka also underwent electroencephalography (EEG). Mean rCBF values did not differ between either amateur boxers or judoka and controls, whereas in professional boxers rCBF was significantly (p<.001) reduced in the whole brain, especially in the frontocentral regions. Healthy subjects, judoka, and amateur boxers showed a similar distribution of global CBF (gCBF, the mean of 32 probes) values, although 12.5% of amateurs had a significantly lower gCBF than controls. Among professional boxers, 25% showed a significantly low gCBF value; in the remaining 75%, gCBF was below the mean value of controls but did not reach statistical significance. Regional hypoperfusion, mainly in the frontocentral regions of both sides, was found in 35% of professional and in 29% of amateur boxers. A correlation between gCBF values and number of official matches was not found in boxers. EEG was normal in all judoka and amateur boxers, but it was abnormal in 3 professionals. This study shows the relevance of the neurophysiological assessment of athletes engaged in violent sports which can cause brain impairment. In fact, while professional boxers may show brain functional impairment in comparison to normal subjects, judoka do not. The lack of correlation between CBF values in boxers and the number of official matches points to the difficulty of taking into account variables, such as the number and the severity of matches during training.